Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1152/jappl.1993.74.3.1016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of detergent aerosol on lung microvascular permeability

Abstract: Noncardiogenic edema fluid often contains high levels of plasma proteins, which may inhibit the function of the lung surfactant complex and thus decrease interstitial hydrostatic pressures. We questioned whether, in the awake and standing animal, displacement of the alveolar surface lining would alter the permeability of the thin and sparsely supported pulmonary capillaries. Sheep prepared with lung lymph fistulae were given an aerosolized detergent (Det) to displace the lung surfactant complex. After the shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The effects of surfactant inactivation on the microvascular endothelial barrier properties have not been unambiguously characterized. Experiments were conducted in dogs (145) and sheep (146) given aerosolized detergent. Microvascular permeability was assessed by analysis of lymph-to-plasma protein ratio during hydrostatic edema caused by increased pulmonary venous pressure.…”
Section: Mechanisms Of Altered Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of surfactant inactivation on the microvascular endothelial barrier properties have not been unambiguously characterized. Experiments were conducted in dogs (145) and sheep (146) given aerosolized detergent. Microvascular permeability was assessed by analysis of lymph-to-plasma protein ratio during hydrostatic edema caused by increased pulmonary venous pressure.…”
Section: Mechanisms Of Altered Permeabilitymentioning
confidence: 99%
“…Microvascular permeability was assessed by analysis of lymph-to-plasma protein ratio during hydrostatic edema caused by increased pulmonary venous pressure. Bredenberg and colleagues found that this ratio fell, indicating an unchanged protein reflection coefficient (145), whereas Wang and coworkers reported that this ratio was unchanged, indicating increased microvascular permeability to proteins (146). The reasons for these discrepancies were unclear.…”
Section: Mechanisms Of Altered Permeabilitymentioning
confidence: 99%
“…Since the initial report of surfactant substi tution for effective treatment of respiratory distress syndrome [1], various clinical trials have proven its value in decreasing mortality rates as well as reducing the incidence of com plications such as pneumothorax [2][3][4], The optimal mode of surfactant administration is K A R Ci F R © 1996 S. Karger AG, Basel l \ / 'V I \ V J c l \ 0006-3126/96/0692-0119S10.00/0 E-Mail karger(a>kargcr.ch F a x + 41 61 306 12 34 still under debate. The standard method of tracheal bolus instillation was derived from animal studies showing that the direct instilla tion of surfactant into the trachea improves oxygenation better and longer than delivery as an aerosol [5,6], However, undesirable side effects of bolus instillation have been re-ported, such as a transient decrease in blood pressure [7][8][9][10], changing cerebral blood flow velocity and cerebral blood volume [8, 9,11,12], as well as arterial carbon dioxide tension (PaCOy) changes [5,10].…”
mentioning
confidence: 99%
“…A 2% detergent solution containing dioctyl sulfosuccinate sodium salt (PN 323586, purity 98%, Sigma, USA), ethanol and saline was used to induce lung injury as described previously . The detergent solution (1–2 mL/kg) was instilled into the lung of the anesthetized animals until it was stable on the ventilator.…”
Section: Methodsmentioning
confidence: 99%